2016
DOI: 10.1063/1.4949240
|View full text |Cite
|
Sign up to set email alerts
|

The enerMENA meteorological network – Solar radiation measurements in the MENA region

Abstract: Abstract. For solar resource assessment of solar power plants and adjustment of satellite data, high accuracy measurement data of irradiance and ancillary meteorological data is needed. For the MENA region (Middle East and Northern Africa), which is of high importance for concentrating solar power applications, so far merely 2 publicly available ground measurement stations existed (BSRN network). This gap has been filled by ten stations in Morocco, Algeria, Tunisia, Egypt and Jordan. In this publication the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 10 publications
0
17
0
4
Order By: Relevance
“…These authors reported that re- Table 1. Instrument description and measured data for each station (from Schüler et al, 2016 analyses often exhibit cloudy conditions while actual conditions are cloud-free and vice versa. Satellite images are another means to getting a synoptic view of the SSI and may supplement radiometric measurements (Lefèvre et al, 2014;Wagner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors reported that re- Table 1. Instrument description and measured data for each station (from Schüler et al, 2016 analyses often exhibit cloudy conditions while actual conditions are cloud-free and vice versa. Satellite images are another means to getting a synoptic view of the SSI and may supplement radiometric measurements (Lefèvre et al, 2014;Wagner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Three of these are dealt with hereafter: the HelioClim-3 databases (version 4 and version 5) and the CAMS Radiation Service (version 2), where CAMS stands for Copernicus Atmosphere Monitoring Service. Each database is available online and has more than several hundred users each year (Thomas et al, 2016a). Validations of each database are routinely performed and their results are published, thus supplying users with up to date knowledge of each database.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a). The two stations belong to the enerMENA meteorological network [47,48]. Both site locations can be described as arid zones with poor vegetation.…”
Section: Saltation Movementmentioning
confidence: 99%
“…For this study and its year 2012, quality controlled data from two stations in Jordan and Tunisia operated by University of Jordan and Centre de Recherché et Technologies de l'énergie (CRTEn) were already available. Details describing all stations can be found in a separate SolarPaces 2015 paper [10].…”
Section: Ground Measurementsmentioning
confidence: 99%